Bank Concentration and Crises - Beck, Thorsten; Demirguc-Kunt, Asli; Levine, Ross (World Bank, Washington, DC, 2014)
The authors study the impact of bank concentration, regulations, and national institutions on the likelihood of suffering a systemic banking crisis. Using data on 79 countries over the period 1980-97, they find that crises are less likely (1) in more concentrated banking systems, (2) in countries with fewer regulatory restrictions on bank competition and activities, and (3) in economies with better institutions, that is, institutions that encourage competition and support private property rights.